PENGARUH KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL TERHADAP KINERJA PEGAWAI (STUDI DI KECAMATAN BIDUK-BIDUK) - Sayugo Adi Purwanto (Universitas Muhammadiyah Kalimantan Timur, 2018)
Effect of Emotional Intelligence and Spiritual Intelligence on Employee Performance (Study in Biduk-biduk Subdistrict). The purpose of this study was to determine emotional intelligence and intelligence of employees in the biduk-biduk subdistrict office of Berau district. This study uses quantitative analysis, reliability analysis, and testing using the T test. Based on the results of these studies it can be seen that each of these variables has emotional and spiritual intelligence which has a positive influence on employee performance variables in the office of biduk-biduk district office. Based on the results of the analysis, the variable with Emotional intelligence variable (X1) has a p value of 0.017 (significant), therefore the value of p <0.05, this means that the variables have a significant effect on employee performance. Based on the results of the analysis, it can be a spiritual variable (X2) has a p value of 0.04 (significant), because the value of p <0.05, this means that the child's intelligence variable has a significant effect on the ability of employees.